2016
DOI: 10.1016/j.molcel.2016.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of Rudimentary Cooperates with Conserved RNA-Processing Factors to Promote Meiotic mRNA Decay and Facultative Heterochromatin Assembly

Abstract: SUMMARY Erh1, the fission yeast homolog of Enhancer of rudimentary, is implicated in meiotic mRNA elimination during vegetative growth, but its function is poorly understood. We show that Erh1 and the RNA-binding protein Mmi1 form a stoichiometric complex called EMC (Erh1-Mmi1 complex), to promote meiotic mRNA decay and facultative heterochromatin assembly. To perform these functions, EMC associates with two distinct complexes, MTREC (Mtl1-Red1 core) and CCR4-NOT. Whereas MTREC facilitates assembly of heteroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
160
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(172 citation statements)
references
References 50 publications
12
160
0
Order By: Relevance
“…The YTH-family protein Mmi1 promotes degradation of meiotic gene transcripts by RNAi and the nuclear exosome 10,11,1518 . Comparing the expression profiles of cells lacking RNAi components or Mmi1 revealed that a majority of the meiotic genes that were upregulated in ago1 ∆ or dcr1 ∆ RNAi mutants (85 out of 152) were also upregulated in mmi1 ∆ (Fig.…”
mentioning
confidence: 99%
“…The YTH-family protein Mmi1 promotes degradation of meiotic gene transcripts by RNAi and the nuclear exosome 10,11,1518 . Comparing the expression profiles of cells lacking RNAi components or Mmi1 revealed that a majority of the meiotic genes that were upregulated in ago1 ∆ or dcr1 ∆ RNAi mutants (85 out of 152) were also upregulated in mmi1 ∆ (Fig.…”
mentioning
confidence: 99%
“…Interestingly, published mass spectrometry data show ARS2 can be phosphorylated at Y172 [81] and Y175 [82] within the DUF3546 domain, suggesting the function of this domain may be regulated post-translationally by phosphorylation. In fission yeast, mutation of F165 in the DUF3546 domain contributes to a temperature sensitive allele [83] . How the DUF3546 domain regulates interactions with RNA requires further investigation.…”
Section: Ars2/serrate Structure/functionmentioning
confidence: 99%
“…In S. pombe, Pir2/Ars2 is required for heterochromatin formation at centromeres, telomeres, heterochromatin domains (HOODs), and a subset of meiotic loci [83,90] . Pir2/Ars2 KD results in decreased histone H3 lysine 9 methylation (H3K9me) levels at these sites, a hallmark of heterochromatin formation [83,90] . The requirement of Pir2/Ars2 for heterochromatin formation at these diverse regions involves several partially overlapping pathways.…”
Section: Ars2 and Heterochromatin Formationmentioning
confidence: 99%
See 2 more Smart Citations